The Effect of Independence, Competence, and Time Pressure on Audit Quality with Professional Skepticism as a Moderating Variable in Semarang City Public Accounting Firms : Case Study of the Implementation of SIKADEKA in the 2024 Election - Vioneta Cattravelly Pandji; Ngurah Pandji Mertha Agung Durya; Ira Septriana; Dwiarso Utomo; Retno Indah Hernawati; Enny Susilowati Mardjono (Malaqbi Publisher, 2026)
This study aims to determine the influence of independence, competence, and time pressure on audit quality, with professional skepticism as a moderating variable, in a case study of the implementation of SIKADEKA for campaign fund audits at a public accounting firm in Semarang. The study involved 50 auditors in the campaign fund audit process using a saturated sampling technique, in which all available members of the population were used as respondents. The study employed classical assumption tests and multiple linear regression analysis. The results presented in the original study indicate that independence and competence do not have a significant effect on audit quality, whereas time pressure has an effect on audit quality. The moderation analysis indicates that professional skepticism does not moderate the effects of independence and competence on audit quality, while professional skepticism moderates the effect of time pressure on audit quality.